THE APPLICATION OF MODERN HRTECHNOLOGIES AS АN EFFECTIVE TOOL IMPROVEMENT OF PERSONNEL MANAGEMENT ENTERPRISES IN UKRAINE - Goncharenko, Iryna (Науковий вісник Полісся, 2017)
Relevance of the research topic. The importance of studying HR-technologies in the system of personnel management has become paramount for modern domestic enterprises. Problem setting. There is a critical need to develop and implement relevant HR-technologies as practical tools in effective personnel management practices at domestic enterprises. Recent research and publications analysis. Within the national research papers exploring effective personnel management methods we should mention the following scholars: L. Balabanov O. Vasilieva, Z. Imasheva, H. Shchokin, O. O. Petrashchak, O. M. Rudenko, L. M. Usachenko, S. V. Shturkhetskyi. Among the foreign authors considerable contribution was made by John Berzin, D. Diakov, P. Loikova, Yu. Pass, O. Svergun, P. Ward D. Ulrich etc. Unresolved issues. Current trends in personnel management at domestic enterprises reveal the low quality of employees and management staff replacement and development process, thus triggering the need to work out new efficient approaches and tools to enhance the HRM system. Research objective. The paper is aimed at developing a well-grounded framework of personnel management optimization system through the use of the proposed tool set. Research findings. The personnel management system is a cornerstone in any enterprise management paradigm, since its effectiveness influences the overall business performance and the achievement of a company objectives. Domestic enterprises in their human resources management strategies were mainly affected by their own experience and partial transfer of some elements of advanced foreign personnel management practices and techniques. The paper substantiates the transition from the traditional personnel management system to the contemporary concept of human resources management through the use of modern tools aimed at continuous improvement of technology, subject to turbulent environments challenges. Conclusion. The introduction of modern HR-technologies is a critical and reliable basis for management process optimization which enables to enhance the existing approaches to personnel selection at domestic enterprises.